2020
DOI: 10.1111/jzo.12769
|View full text |Cite
|
Sign up to set email alerts
|

Bat‐borne viruses in Africa: a critical review

Abstract: In Africa, bat-borne zoonoses emerged in the past few decades resulting in large outbreaks or just sporadic spillovers. In addition, hundreds of more viruses are described without any information on zoonotic potential. We discuss important characteristics of bats including bat biology, evolution, distribution and ecology that not only make them unique among most mammals but also contribute to their potential as viral reservoirs. The detection of a virus in bats does not imply that spillover will occur and seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 159 publications
(263 reference statements)
1
50
0
1
Order By: Relevance
“…The COVID-19 pandemic, like the SARS-CoV 1 and Ebola epidemics, likely originated from human consumption of wild animals. Live wildlife markets create opportunities for pathogens to infect naïve domestic species or humans and trigger new diseases 41,42 . In Africa, particularly in the tropical forest biome, bushmeat markets expose human populations to species identified as high risk for pathogen spillover, such as primates, bats and rodents 43 .…”
Section: Risk Of Future Outbreaks Due To Human Impacts On Naturementioning
confidence: 99%
“…The COVID-19 pandemic, like the SARS-CoV 1 and Ebola epidemics, likely originated from human consumption of wild animals. Live wildlife markets create opportunities for pathogens to infect naïve domestic species or humans and trigger new diseases 41,42 . In Africa, particularly in the tropical forest biome, bushmeat markets expose human populations to species identified as high risk for pathogen spillover, such as primates, bats and rodents 43 .…”
Section: Risk Of Future Outbreaks Due To Human Impacts On Naturementioning
confidence: 99%
“…Singular spill-over events of lyssaviruses other than RABV from bats to terrestrial mammals also have been reported [14][15][16][17][18][19]. Despite increasing recognition of their importance, relatively little is known about the dynamics of lyssavirus infections in their natural hosts, bats [13,20,21]. Based on the recurrent finding of high seroprevalences in some freeranging bat populations (Table 3.2 in [22]), a number of researchers have hypothesized that bats, in contrast to other mammals, can survive a productive lyssavirus infection, i.e an infection where lyssavirus reaches the brain and is subsequently excreted from the oral cavity [23].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the recurrent finding of high seroprevalences in some freeranging bat populations (Table 3.2 in [22]), a number of researchers have hypothesized that bats, in contrast to other mammals, can survive a productive lyssavirus infection, i.e an infection where lyssavirus reaches the brain and is subsequently excreted from the oral cavity [23]. In contradiction, there is no indication from experimental infections in bats that this occurs and bats seem, like other species, unable to survive infection of the brain, which appears to always result in fatal rabies [21,48]. Experimental infections in bats have been performed mainly with four lyssaviruses: RABV, Australian bat lyssavirus, and European bat lyssaviruses 1 and 2 [49].…”
Section: Introductionmentioning
confidence: 99%
“…This epidemiological role was again confirmed in 1994 via their role in the spread of Hendra virus among horses and Nipah, SARS, and filoviruses (Marburg, Ebola, and Mengla virus) among humans (Peiris et al 2004;Johnson et al 2010;Li et al 2005). Bat examination revealed the presence of viruses from most of the known viral families, including Rhabdoviruses, paramyxoviruses, filoviruses, and coronaviruses without showing any clinical signs (Wang and Cowled 2015;Markotter et al 2020). The simultaneous presence of various viral genomes in bats enables the permanent evolution of new unknown viruses in bats (Woo et al 2012).…”
Section: Bats Antiviral Innate Immunity and Coronavirusesmentioning
confidence: 93%
“…About 75% of the human emerging infectious diseases are zoonotic in origin and are mainly associated with wild animals (Markotter et al 2020). The last few days of the year 2019 showed the emergence of a new epidemic of coronavirus (severe acute respiratory syndrome -2; SARS-CoV2).…”
Section: Introductionmentioning
confidence: 99%